Սեփականության իրավունքի առաջացման հիմքերի ընդհանուր բնութագիրը և դասակարգումը - Թադեվոսյան, Արման
правусобственности, применяет понятия «возникновение» и «приобретение». При использовании слова «приобретение» упор делается на субьекта права собственности. А вот слово «возникновение» используется не для субъекта права, а для субъективного права, возникающего у субъекта. Гражданский кодекс РА не дает четкого определения, что является первоначальной основой возникновения права собственности, и которое является производным. Это приводит к ряду разногласий среди ученых-юристов. Мы видим необходимость, дать эту классификацию четкую и полноценную законодательную фиксацию. Civil legislation relating to the right of ownership applies the concepts of “emergence” and “acquisition. When using the concept “acquisition”, the emphasis is on the subject of the right of ownership. While the word “emergence” is used not for the subject of the right, but for the subjective right arising from the subject. The Civil Code of the Republic of Armenia does not give a clear definition of what basis is the initial for the emergence of the right of ownership, and which is derivative. This leads to several disagreements among legal scholars. We see the need to give this classification a clear and complete legislative fixation.
Keywords: Քաղաքագիտություն; Իրավագիտություն